How Nurses in Johannesburg Address Intimate Partner Violence in Female Patients: Understanding IPV Responses in Low- and Middle-Income Country Health Systems. Issue 11 (June 2017) - Sprague, Courtenay; Hatcher, Abigail M.; Woollett, Nataly; Black, Vivian
One in three women, globally, experiences intimate partner violence (IPV). Although 80% of the world's population resides in the low- and middle-income countries (LMICs), health system responses to IPV are poorly understood. In 2013, the World Health Organization released new guidelines for IPV but universal screening was not recommended in LMICs due to perceived lack of capacity and insufficient evidence. South Africa, with IPV prevalence estimated at 31% to 55%, offers a window into LMIC health systems. South African women seek health care for partner abuse, yet no guidelines exist to direct providers. This research aimed to understand how and why nurses respond to IPV. Using a descriptive design, 25 nurses from five health facilities were interviewed, generating rich narratives of provider actions. Themes were coded and analyzed. An iterative process of constant comparison of emergent data was undertaken to verify and confirm final themes. In the absence of IPV guidelines, nurses employed interventions characterized as counseling, ascertaining abuse, and referral. Nurses' actions were motivated by fear for patients' survival, perceived professional obligations, patients' expectations of receiving treatment, personal experiences of IPV, and weak police responses to IPV. Findings indicated nurses were responding to IPV in a routine manner, yet comprehensive guidelines remain essential to govern and locate their actions within the framework of a public health response. South Africa yields lessons for enhancing understanding of IPV responses in LMICs, while contributing to a slim evidence base of the "how" and "why" of provider actions toward IPV in patients.